Rancang Bangun Prototype Berbasis WEB Sebagai Implementasi Praktik Wirausaha Mahasiswa di Kota Semarang - Mariana Kristiyanti (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
In Semarang, college growth offers the entrepreneurial traits for educative competitor of expanding very fast. Mostly, college has used the information system to market result of practice entrepreneurial all its student, but on the way, growth practice the entrepreneurial among student impress tardy and product and also service which they yield, not yet optimal of its information spreading. Designedly develop build the in wrought prototype system accomodating all result practice the wirausaha competitor educated by which is gone the round of in various college in Semarang, expected can give the information widely hit result of practice entrepreneurial in web. And indirectly, the web can become the individuality of Semarang providing information of result of child masterpiece nation passing the Website. Design to develop, build the prototype base on the Web to find the product yielded by all students in Semarang, representing picture of Information System to be made later. Research method used by Observation to College offering program of entrepreneurial and interview, while designing to develop build the Prototype of result of this practice entrepreneurial use the Flowchat System.